Sub-10 nm Imaging of Nucleic Acids Using Spectroscopic Intrinsic-Contrast Photon-Localization Optical Nanoscopy (SICLON) - Eshein, Adam (Opt Lett, 2018)
Elucidating chromatin structure in vitro requires resolution below 10 nm to visualize the mononucleosome and has been an ongoing challenge. In this work, we achieve sub-10 nm imaging of nucleic acids via Spectroscopic Intrinsic-Contrast photon-Localization Optical Nanoscopy (SICLON) without the use of external labels. SICLON leverages two key innovations: using endogenous nucleotides as the emission source, and a custom-made imaging system that can simultaneously record the position and optical spectra of emitting molecules. With a novel spectral-regression algorithm that identifies the spectroscopic fingerprints of neighboring molecules that were previously indistinguishable, we demonstrate the utility of SICLON by visualizing unlabeled polynucleotides and linear single stranded DNA fibers with a resolution of 6.2 nm.